A Cutting Sequencing Approach to Modular Manufacturing - Özdemir, Rifat Gürcan; AKTİN, AYŞE TÜLİN (Emerald Group Publishing Limited, 2004)
In this study, a two‐stage algorithm is developed for the cutting sequencing problem in a modular manufacturing system consisting of four basic workstations. Since the flexibility of the system is dependent upon the cutting stage of raw materials, the study focuses particularly on this workstation. In the first stage of the algorithm, an integer linear programming model is used to determine the number of hardboards that will be cut. The model is tested with two different objective functions. In the second stage, a heuristic which takes into account the due date of the products is developed to obtain the real‐time sequencing of these cutting patterns on the shop floor. The algorithm is further implemented in a furniture manufacturer that operates on a make‐to‐order basis. The results of the existing and proposed system are compared, and the proposed algorithm is found to provide a useful tool in such a real‐life planning problem.
Keywords: Manufacturing systems; Flexible manufacturing systems; Sequential production; Linear programming